A Look at Teaching Work from the Paradigm of Ecocriticism and Ecofeminism - Jorquera-Martinez, C (UNIV ICESI, 2025)
Thiswork aims to describe the perception ofsecondaryeducation teachers and undergraduate students about the environmental problem and its relationship with gender issues. Forthis, we applied surveys to two groups: Spanish Language and Communications teachers at Los Lagos region (Chile) and undergraduate students throughout Chilefrom the perspective of ecocriticism and ecofeminism. As a result, in both cases, a significant gap between the idealized perception of the natural world and the real experience was found. The case of teachers is especially significant because they point out the differences between initial teachertraining and the realityofdailyteachingwork. Both groups highlightthe lackof a clearand articulated connection between environmental and gender issues.